Morphometric evaluation of fetal stomach in alpaca (Vicugna pacos) - Flores-Tintaya, Wilian; Quispe-Gutiérrez, Ulises Sandro; Alva-Villavicencio, Gizely; Navarrete-Zamora, Miluska Beatriz (Revista Científica de la Facultad de Ciencias Veterinarias, 2022)
The raising of alpacas (Vicugna pacos) in Peru constitutes one of the most resources for the survival and food security of the high Andean inhabitants. The digestive anatomy of the alpaca is not yet fully described to explain the physiological and nutritional processes. To describe the structure of the fetal stomach of the alpaca, six fetuses of Huacaya alpacas obtained from the slaughterhouse, distributing two fetuses (male and female) for each third of gestation. The fetuses were dissected exposing the stomachs, measurements of the length and width of the three compartments (C) were made, and the sulci and cells of C1 were also described. The analysis of variance was carried out considering the effect of sex, gestational age, C and their interactions, whose response variable was the length and width of the stomach C. There was no interaction (P>0.05) for any of the study variables. The length and width of the three Cs of the fetal stomach were similar in males and females (P>0.05). The length and width of the C were smaller (P≤0.05) in the first third of pregnancy, increasing the measurements in the second and last third of the pregnancy. The length of C3 was greater (P≤0.05) than C1 and C2, while the width of C1 was greater (P≤0.05) than C2 and C3. In C1 of the dorsal sac, there were more perpendicular furrows and cells in the last third of gestation. In conclusion, the sizes of the C of the fetal stomach of the alpaca increased as gestational age advanced. Furthermore, in C1, there were more perpendicular furrows and cells in the last third of gestation.